Single-entity Ti3C2Tx MXene electro-oxidation. (March 2022) - Nayak, Pranati; Yang, Minjun; Wang, Zhiwei; Li, Xiuting; Miao, Ruiyang; Compton, Richard G.
Highlights: First-ever study on quantitative innate electro-oxidation behavior of single Ti3 C2 Tx MXene via single-entity electrochemistry (SEE). The extent of electro-oxidation depends on the applied electrode potential. At the highest applied potential (ca. 1.3 V), about 2% of total ti oxidises in a single Ti3 C2 Tx particle. A fair resemblance on the oxidation behavior of single entity Ti3 C2 Tx MXene with an ensemble of particles. Abstract: We quantify the innate electro-oxidation behavior of a single Ti3 C2 Tx MXene particle by Single-Entity Electrochemistry. MXene undergoes irreversible oxidation at potentials greater than 0.3 V (vs. SCE), with the extent of oxidation dependant on the applied potential. A close correlation is seen with ensembles of drop-cast particles with submonolayer coverage. Graphical abstract: Image, graphical abstract "Ti3 C2 Tx MXene particle on collision with potentiostated electrode surface renders surface oxidation through a visible current spike in the voltammogram."